Pemberdayaan UMKM Cihil Food melalui Inovasi QR Code - Maharani Dinda Zakiyah; Faizatul Ulya; Dany Boy Surbakti; Deden Satria Asih Supriyadi; Agief Julio Pratama; M. Iqbal Nurulhaq; Tri Budiarto; Widya Hasian Situmeang; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
UMKM are one form of micro, small, and medium enterprises that are formed because of someone's personal desire. UMKM actors must strive to increase competitive advantage, UMKM must increase adaptation to currently developing technology, increase the ability to use social media and digital marketing, increase product innovation, and expand the market are some of the right steps that are worthy of being taken by UMKM actors. This is worthy of being implemented in order to increase the selling value of UMKM, especially in order to be able to compete with foreign products that are increasingly flooding the national market, considering that UMKM are an economic sector that is able to reduce unemployment (Sudaryanto. 2011). UMKM through digital marketing development can help the community increase income so that they can follow the development of entrepreneurship. The method in implementing UMKM empowerment activities is carried out using observation, surveys, questionnaires, and interviews. The results of this empowerment are that this activity was attended by UMKM Cihil Food which has 10 members, socialization of social media and digital marketing through the creation of a special website for UMKM Cihil Food which is combined with Barcode (QR) innovation. Based on this activity, it was found that in improving the welfare of UMKM, what must be done is to make maximum use of technology, improve the community economy, and improve human resources.